1982
DOI: 10.1002/1520-6807(198210)19:4<558::aid-pits2310190426>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of first-year, fifth-year, and former teachers on efficacy, ego development, and problem solving

Abstract: Differences in first-year (N=50), fifth-year (N=49) and former ( N = 3 0 ) teachers on measures of efficacy, ego development, and problem solving were analyzed. The three groups were graduates from the same university who responded to a written survey. ANOVA was used for each variable across all groups, with an alpha level of .05, and the Schefle multiple range test was used to determine significance between groups. On measures of efficacy and ego development, both first-year and fifth-year teachers scored sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
10

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 5 publications
2
58
0
10
Order By: Relevance
“…The concept of self-efficacy was introduced by Bandura (1977) and was quickly shown to be a useful predictor of a teacher's classroom performance, academic performance of her students and overall job satisfaction [Ashton, Webb 1986;Pajares 1997;Canrinus et al 2012]. Besides that, in some studies it was demonstrated that teachers with higher self-efficacy are more likely to stay in teaching [Glickman, Tamashiro 1982;Swanson 2012;Vieluf, Kunter, van der Vijver 2013].…”
Section: Empirical Data On Teacher Turnovermentioning
confidence: 99%
“…The concept of self-efficacy was introduced by Bandura (1977) and was quickly shown to be a useful predictor of a teacher's classroom performance, academic performance of her students and overall job satisfaction [Ashton, Webb 1986;Pajares 1997;Canrinus et al 2012]. Besides that, in some studies it was demonstrated that teachers with higher self-efficacy are more likely to stay in teaching [Glickman, Tamashiro 1982;Swanson 2012;Vieluf, Kunter, van der Vijver 2013].…”
Section: Empirical Data On Teacher Turnovermentioning
confidence: 99%
“…As Berne (1996) has suggested, stroking is a need for survival and this fact never changes across genders or through the years. It has been shown in a raft of studies (Allinder, 1994;Glickman & Tamashiro, 1982;Guskey, 1988;Pajares, 2002;Soodak & Podell, 1997) that highly self-efficacious teachers can lead students to achieve their educational goals more successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Coladarci (1992) found that teachers with a high sense of self-efficacy are highly committed to their profession. Glickman and Tamashiro (1982) found that teachers with a low sense of self-efficacy tend to leave the teaching profession. In a study by Jones (1986) about socialization tactics, self-efficacy, and newcomers' adjustment to organizations, it was concluded that self-efficacy regulates the learning process of a newcomer and that socialization tactics produce a stronger protective role orientation when newcomers possess a low level of self-efficacy.…”
Section: Self-efficacymentioning
confidence: 99%